Integration of Maritime and Islamic Values in Coastal Islamic Education Curriculum: A Thematic Literature Review - Sutikno, Sutikno; Adie, Ciska Fitria; Eko Saputro, Danang; Irvansyah, Moh. Faiz (UIR Press, 2026)
This study aims to examine the integration of maritime and Islamic values ​​and their relevance as a basis for developing an Islamic education curriculum in coastal areas. The study used a qualitative approach with thematic library research. Data were obtained from reputable journal articles, academic books, research reports, and policy documents relevant to Islamic education, coastal local wisdom, and maritime values, published in the last ten years. Data analysis was conducted using the Braun and Clarke thematic analysis model through the stages of coding, grouping themes, and interpreting meaning. The results show that maritime values ​​such as work ethic, discipline, courage, social solidarity, and ecological concern have substantial alignment with Islamic values, especially the concepts of caliph, trustworthiness, gratitude, hard work, and the prohibition of environmental damage. The integration of these values ​​is relevant for developing a coastal Islamic education curriculum that is contextual, ecological, and oriented towards the formation of students' religious-social character. The research conclusion confirms that the integration of maritime and Islamic values ​​is a strategic approach in responding to the socio-ecological needs of coastal communities and can be a conceptual basis for the development of a sustainable Islamic education curriculum.